2000
DOI: 10.1034/j.1600-0560.2000.027008413.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of intravascular large B‐cell lymphoma mimicking erythema nodosum: the importance of multiple skin biopsies

Abstract: This is a unique case for two following reasons: 1) the first biopsy revealed non-specific findings compatible with erythema nodosum; and 2) before the treatment, the nodules regressed spontaneously. Dermatologists should take multiple skin biopsies for EN lesions with the non-specific histopathological findings not to refute the existence of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 21 publications
0
20
1
Order By: Relevance
“…10,11 In our patient, induration was a minor feature while telangectases were marked. Unusual skin findings have included generalized telangectasia, 12 asymptomatic purpuric patches, 13 panniculitis-like lesions with spontaneous regression, 14 and Kaposi sarcoma-like lesions. 4 Because of the variation in cutaneous findings, the differential diagnosis of intravascular lymphoma may be broad (Table I).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…10,11 In our patient, induration was a minor feature while telangectases were marked. Unusual skin findings have included generalized telangectasia, 12 asymptomatic purpuric patches, 13 panniculitis-like lesions with spontaneous regression, 14 and Kaposi sarcoma-like lesions. 4 Because of the variation in cutaneous findings, the differential diagnosis of intravascular lymphoma may be broad (Table I).…”
Section: Discussionmentioning
confidence: 98%
“…16 Autopsy reports typically show multisystem involvement with pulmonary failure, cerebrovascular infarcts, and brain metastasis being prominent. 2,3,5,14 More recently, combination chemotherapy has been reported to induce long-term survival or complete remission. In a review of 35 patients treated with chemotherapy, DiGuiseppi et al 17 reported long-term remission (up to 48 months of followup) in 43% of patients treated with chemotherapy regimes typically used for high-grade lymphomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a clinical perspective, the variably livedoid erythema can generate differential considerations for vasculopathic states or reactive erythemas Ponzoni et al 2007 ). The indurated plaques and nodules can be confused with panniculitis (Kiyohara et al 2000 ) or with other neoplasms. The polymorphous cutaneous presentations of intravascular lymphoma have led to varied clinical impressions ranging from cellulitis (Roglin and Boer 2007 ) to vasculitis to vascular tumors (e.g., Kaposi's sarcoma) (Demirer et al 1994 ) to keratinocytic tumors (e.g., squamous cell carcinoma) (Stroup et al 1990 ).…”
Section: Pyoderma Gangrenosum Associated With G-csfmentioning
confidence: 99%